The effect of bolus volume on laryngeal closure and UES opening in swallowing: Kinematic analysis using 320‐row area detector CT study. (3rd October 2017) - Shibata, S.; Inamoto, Y.; Saitoh, E.; Kagaya, H.; Aoyagi, Y.; Ota, K.; Akahori, R.; Fujii, N.; Palmer, J. B.; González-Fernández, M.
Summary: This study investigated the effects of three different volumes of honey‐thick liquid on the temporal characteristics of swallowing. Twenty‐six healthy subjects (15 males, 11 females) underwent 320‐row area detector CT scan while swallowing 3, 10 and 20 mL of honey‐thick liquid barium. Three‐dimensional images were created at 10 images/s. Kinematic events involving six structures (velopharynx, hyoid bone, epiglottis, laryngeal vestibule (LV), true vocal cords (TVC), upper esophageal sphincter (UES)) and timing of bolus movement were timed using frame by frame analysis. The overall sequence of events did not differ across three volumes; however, increasing bolus volume significantly changed the onset and termination of events. The bolus head reached to pharynx and esophagus earlier and the duration of bolus passing through UES was significantly longer in 10 and 20 mL compared to 3 mL ( P < .05). Consequently, the onset of UES opening was significantly earlier with increased volume ( P < .05). LV and TVC closure occurred later in 20 mL compared to 3 mL ( P < .05). These changes in motion of pharynx and larynx appeared to promote swallow safety by preventing aspiration, suggesting that anatomical structure movements adapt in response to bolus volume. Our findings also suggest that the pharyngeal swallow behaviours may be modified by afferents in the oral cavity. The three‐dimensional visualization and quantitative measurements provided by 320‐ADCT provide essential benchmarks for understanding swallowing, both normal and abnormal.